Perancangan Arsitektur Enterprise Fase Arsitektur Bisnis dengan TOGAF ADM (Studi Kasus: MSI UNAMA) - Sadikin, Ali; Lola Yorita Astri; M. Riza Pahlevi (LPPM STIKOM Dinamika Bangsa, 2024)
This research explores the application of the TOGAF ADM 9.0 framework in designing an enterprise architecture for the Master of Information Systems (MIS) program at Universitas Dinamika Bangsa Jambi. The study focuses on key phases such as the preliminary phase, architecture vision, business architecture, information systems architecture, and technology architecture, aiming to develop an integrated information system. The MIS program faces several operational challenges, including ineffective promotional strategies, a partially functional e-learning system, and a lack of comprehensive digitalization in academic management and assessment processes. To address these issues, the study proposes the development of web- and mobile-based applications that support processes such as promotion, student admissions, teaching, and academic and administrative management. The resulting architecture design includes an integrated application portfolio catalog, which is expected to enhance the efficiency and quality of academic services within the program.